Analisis Cost Structure Dengan Metode Variable Costing Guna Meningkatkan Laba Studi Kasus Di Rumah Sakit Swasta Di Jawa Timur - Safiara Aura Nadifatus Solikhah; Eni Srihastuti; Agus Athori (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Cost Structure consists of fixed costs and variable costs in producing hospital services. Variable costing is a strategic method used to classify hospital costs. The research aims to analyze the cost structure using the variable costing method in increasing profits of private hospitals in East Java, with financial data for 2022. This research is limited to cost structure analysis using the variable costing method in private hospitals in East Java. This research uses data secondary in the form of cost and profit and loss reports from private hospitals in East Java in 2022. Data collection techniques include interviews and documentation. The data will be processed using quantitative descriptive analysis, and the data analysis steps include identifying cost structures, identifying variable costing, and comparing profit and loss using the variable costing method and the hospital method. Analysis of the profit and loss report shows the differences between the Private Hospital method in East Java and the method variable costing. The variable costing method uses the cost of goods sold and does not include the cost of goods manufactured. The difference in profit generated is IDR. 81,152,791,-.